2015
DOI: 10.1371/journal.pone.0124868
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of the Larval Chalkbrood Disease Pathogen Ascosphaera apis (Ascomycota: Eurotiomycetes: Ascosphaerales) in Adult Bumble Bees

Abstract: Fungi in the genus Ascosphaera (Ascomycota: Eurotiomycetes: Ascosphaerales) cause chalkbrood disease in larvae of bees. Here, we report the first-ever detection of the fungus in adult bumble bees that were raised in captivity for studies on colony development. Wild queens of Bombus griseocollis, B. nevadensis and B. vosnesenskii were collected and maintained for establishment of nests. Queens that died during rearing or that did not lay eggs within one month of capture were dissected, and tissues were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 40 publications
(50 reference statements)
0
29
0
1
Order By: Relevance
“…Additionally, we found that BQCV isolated from the fungus Ascosphaera apis from honey bees in Maryland clustered with our New York honey bee and native bee samples, illustrating the close relatedness of the virus and potential for virus crossover between fungal and bee species. Some bee viruses can infect and replicate within Ascosphaera apis, which causes chalkbrood in honey bees (Li et al, 2014) and is known to be pathogenic in bumble bees (Maxfield-Taylor et al, 2015). Both pathogenic and saprotrophic strains have been found in solitary bees (Osmia cornifrons) (Hedtke et al, 2015).…”
Section: Host Patternsmentioning
confidence: 99%
“…Additionally, we found that BQCV isolated from the fungus Ascosphaera apis from honey bees in Maryland clustered with our New York honey bee and native bee samples, illustrating the close relatedness of the virus and potential for virus crossover between fungal and bee species. Some bee viruses can infect and replicate within Ascosphaera apis, which causes chalkbrood in honey bees (Li et al, 2014) and is known to be pathogenic in bumble bees (Maxfield-Taylor et al, 2015). Both pathogenic and saprotrophic strains have been found in solitary bees (Osmia cornifrons) (Hedtke et al, 2015).…”
Section: Host Patternsmentioning
confidence: 99%
“…The more elderly beekeepers showed more experience and understanding in the interpretation of the findings of these inspections. However, there was a common misconception that moulds indicated cold instead of chalkbrood as the primary problem [49][50][51]. This showed that inspection alone was not sufficient in disease diagnosis.…”
Section: Perceived Effect Of Pests and Diseases On Coloniesmentioning
confidence: 99%
“…There are several documented cases of pathogen transmission from honey bees to bumble bees in Europe and North America [106][107][108][109][110][111]. The honey bee pathogen A. apis has been detected within the colonies of many captive-reared bumble bees species, including B. griseocollis, B. nevadensis, B. vosnesenskii, and B. terrestris [112]. A recent study reveals that infected colonies of B. terrestris showed symptoms similar to that of chalkbrood disease in honey bees [100].…”
Section: Implications For Bumble Bee Healthmentioning
confidence: 99%
“…Another potential route of exposure is the use of infected honey bee-collected pollen as diet for the developing colonies reared in captivity [118]. Contaminated honey bee pollen, which often carries bumble bee pathogens, has been reported to cause widespread infections at commercial rearing facilities and can lead to rapid declines in bumble bee populations [112,[118][119][120][121]. The risk of pathogen spillover from the release of such infected colonies to native bee populations poses a significant threat to the health of wild bees [35,38,41,118,120,122,123].…”
Section: Implications For Bumble Bee Healthmentioning
confidence: 99%